Association of Birth Weight with Gestational Age and Maternal Measles Antibodies - Ahmadu, BU; Shemiya, Y; Anita, G; Ubong, S; Abdulrahman, B; Amina, B; Iranyang, Y; Rabi, Z; Chekwube, MA; Fatima, MU; Gidado, A (Journal of Nepal Paediatric Society, 2015)
Introduction: Maternal measles antibody (MMA) offers protection against measles in early childhood, however, certain determinants of this antibody lives much to be desired. The aim of the study were to determine the association between birthweight (BW) and gestational age (GA), to assess the relationship between BW and MMA, to correlate GA with MMA and to examine the combined effects of BW and GA on MMA. Material and Methods: The work was a hospital-based cross-sectional descriptive study. Babies were enrolled using systematic random sampling method. The babies BW was measured using the bassinet scale; enzyme linked immunosorbent assay was used to determine MMA. GA of babies was determined using the mothers' last menstrual period (LMP) or by Dubowitz score or by Obstetric ultrasound scan. Data were analysed using SPSS statistical software version 16, Illinois, Chicago USA and a computer program for epidemiologist PEPI version 3.01. Spearman’s correlation (rho), Kendall’s rank correlation (tau b) and Jonckheere-Terpstra test of association of ordinal variables were determined. Univariate analysis was used to investigate the combine effects of BW and GA on MMA. Likely-hood ratio Chisquare (?2) was used for categorical data. Goodman-Kruskal index rank order of predictive association (tau) of ordinal data was also calculated. Results: 200 babies were enrolled, 101 (50.5%) were males and 99 (49.5%) females. 169 babies (84.5%) had normal BW, 117 (58.5%) were delivered at term. The mean BW was 3.04 (0.58) at 95% CI (2.96 – 3.12) kg. Association between BW and GA was significant (p=0.003), the predictive value for the association was also significant (p=0.039). Significant correlation was also observed between GA and MMA (p<0.001). Conclusions: There was a significant association between BW and GA and MMA correlated well with GA. J Nepal Paediatr Soc 2015;35(1):6-12